2014
DOI: 10.1128/jvi.00508-14
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Features of the PB2 627 Domain Impact Influenza Virus Polymerase Function and Replication

Abstract: Successful replication of influenza virus requires the coordinated expression of viral genes and replication of the genome by the viral polymerase, composed of the subunits PA, PB1, and PB2. Polymerase activity is regulated by both viral and host factors, yet the mechanisms of regulation and how they contribute to viral pathogenicity and tropism are poorly understood. To characterize these processes, we created a series of mutants in the 627 domain of the PB2 subunit. This domain contains a conserved "P[F/ P]A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 62 publications
4
28
0
Order By: Relevance
“…46 Based on structural biology, the PB2 domain has a key exterior, positively charged residue at the 627 position within a flexible loop that partially wraps around an alpha helix to form what is known as a phi-loop. 53 Importantly, this residue is in the middle of a set of highly conserved, basic residues forming a net positive charge. A signature structural element is the conserved P[F/P]AAAPP motif on the N-terminal side of the 627 residue that is part of the alpha helix previously described.…”
Section: Structure and Function Of The Polymerases Of Respiratory Rnamentioning
confidence: 99%
“…46 Based on structural biology, the PB2 domain has a key exterior, positively charged residue at the 627 position within a flexible loop that partially wraps around an alpha helix to form what is known as a phi-loop. 53 Importantly, this residue is in the middle of a set of highly conserved, basic residues forming a net positive charge. A signature structural element is the conserved P[F/P]AAAPP motif on the N-terminal side of the 627 residue that is part of the alpha helix previously described.…”
Section: Structure and Function Of The Polymerases Of Respiratory Rnamentioning
confidence: 99%
“…Viruses stably encoding a C-terminal FLAG tag on PB2 required duplication of a portion of the PB2 open reading frame to maintain a contiguous packaging signal and were engineered following the strategy of Dos Santos Afonso et al (31). WSN, WSN(PB2-FLAG), or reassortants encoding PB2-FLAG, PB1, PA, and NP derived from A/green-winged teal/OH/175/1983 (S009) or A/New York/312/2001 (NY312) were rescued in transfected HEK293T cells and amplified, and their titers were determined as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…The smFRET results suggest that the population of the closed state of 627-NLS is reduced to very low levels in complex with importin corroborating the model by which the open state is the binding competent form. Experiments carried out on four importin isoforms (1, 3, 5 and 7) indicate that this mechanism is general for PB2 binding to all members of the importin  family.A recent study of residues involved in enhanced polymerase activity in 627-NLS found that mutation of the basic 650 residue, an essential constituent of the stabilizing salt bridge, resulted in efficient nuclear import but reported a lack of polymerase activity in the nucleus 38. This supports our observation that the open form mediates interaction with importin , and further supports the recent observation that the closed form is essential for function within the context of the reconstituted polymerase-RNA complex, where it has been proposed to play a crucial role in interaction with transcribed RNA in the polymerase exit tunnel 10.…”
mentioning
confidence: 98%